2018
DOI: 10.3390/brainsci8110201
|View full text |Cite
|
Sign up to set email alerts
|

Borderline Personality Disorder (BPD): In the Midst of Vulnerability, Chaos, and Awe

Abstract: Borderline personality disorder (BPD) is a chronic psychiatric disorder characterized by pervasive affective instability, self-image disturbances, impulsivity, marked suicidality, and unstable interpersonal relationships as the core dimensions of psychopathology underlying the disorder. Across a wide range of situations, BPD causes significant impairments. Patients with BPD suffer considerable morbidity and mortality compared with other populations. Although BPD is more widely studied than any other personalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 85 publications
2
28
0
6
Order By: Relevance
“…The pathophysiology of BPD is believed to be multifaceted, involving psychosocial, genetic and neurobiological factors [47]. A growing number of reports suggest abnormalities in the endocrinology, neurochemistry, neuroanatomy and neurophysiology of patients with BPD.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology of BPD is believed to be multifaceted, involving psychosocial, genetic and neurobiological factors [47]. A growing number of reports suggest abnormalities in the endocrinology, neurochemistry, neuroanatomy and neurophysiology of patients with BPD.…”
Section: Discussionmentioning
confidence: 99%
“…Inappropriate behavioral stress responses are clinically well characterized in BPD, with impulsivity, emotion dysregulation and problems with emotion perception and dissociation being core features of BPD symptomatology 13,14. These are often considered to be maladaptive coping mechanisms, or avoidance strategies which may develop in the context of previously experienced trauma, particularly in early life.15 Such altered stress responses have also been well documented in BPD at the structural, neurological, and neurobiological level which is believed to underly the maladaptive behavioral and cognitive outcomes presented in BPD.16…”
Section: Rethinking Bpd As a Neurodevelopmental Stress-related Disordermentioning
confidence: 99%
“…Structurally, chronic stress has been shown to alter gray matter volume in brain regions central in stress responsivity; the amygdala becomes enlarged, and the hippocampus decreases, resulting in changes to fronto-limbic brain circuitry known to be involved in stress perception, emotion processing, and regulation.19 Neuroimaging studies have demonstrated that individuals with BPD have volumetric reductions in the hippocampus, amygdala, and medial temporal lobes bilaterally,20 brain regions central in stress regulation, and emotional regulation,16 and compared to controls, show increased activation of the left amygdala and posterior cingulate cortex, and blunted prefrontal cortex activation, during the processing of negative emotional stimuli.21…”
Section: Trauma and The Neurodevelopment Of The Stress Responsementioning
confidence: 99%
“…Borderline personality disorder is one of the most prevalent disorders in clinical settings, and evidence suggests that it is more common compared with schizophrenia (Gunderson, 1984 ; Zimmerman et al, 2005 ; Linehan, 2018 ; Zanarini, 2018 ; Chapman et al, 2019 ). The past empirical evidence showed 3–6% prevalence of BPD globally (Swartz et al, 1990 ; Torgersen et al, 2001 ; Regeer et al, 2004 ; Grant et al, 2008 ; Lenzenweger, 2008 ; Merikangas et al, 2011 ; Shen et al, 2017 ; Kulacaoglu and Kose, 2018 ; Sher et al, 2019 ). Despite high inpatients prevalence rates, according to several clinicians, BPD is often overlooked and incorrectly diagnosed or underdiagnosed in different mental health treatment centers globally (Leichsenring et al, 2011 ; Ellison et al, 2018 ; Gunderson et al, 2018 ; Linehan, 2018 ; Wlodarczyk et al, 2018 ; Chapman et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%